2009
DOI: 10.1159/000254378
|View full text |Cite
|
Sign up to set email alerts
|

Mouth and Nasal Inspiratory Pressure: Learning Effect and Reproducibility in Healthy Adults

Abstract: Background: Inspiratory muscle strength measurements have become a cornerstone in monitoring neuromuscular disorders. Usually, sniff nasal inspiratory pressure (SNIP) and maximal inspiratory pressure (MIP) are performed. To our knowledge the session-to-session learning effect has rarely been evaluated for MIP performance and has never been done for SNIP performance. Objectives: We hypothesized that the sniff manoeuvre was natural and did not need to be learned, whereas the Muller manoeuvre, used for MIP measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 61 publications
3
29
0
2
Order By: Relevance
“…We therefore adopted this approach in our study, in line with the recommendations of LOFASO et al [13] for the longitudinal monitoring of inspiratory muscle strength. As a result, the SNIP repeatability in our BMD/DMD children was better than that observed in healthy children (16-17%, 10 sniffs without visual feedback) [21] or in 5-50-year-old subjects with neuromuscular disorders (20%, 10 sniffs without visual feedback) [9] but close to that reported in healthy adults (6% and 10% with 10 and 12 sniffs, respectively, without visual feed-back) [22,23].…”
Section: Baseline Datasupporting
confidence: 56%
“…We therefore adopted this approach in our study, in line with the recommendations of LOFASO et al [13] for the longitudinal monitoring of inspiratory muscle strength. As a result, the SNIP repeatability in our BMD/DMD children was better than that observed in healthy children (16-17%, 10 sniffs without visual feedback) [21] or in 5-50-year-old subjects with neuromuscular disorders (20%, 10 sniffs without visual feedback) [9] but close to that reported in healthy adults (6% and 10% with 10 and 12 sniffs, respectively, without visual feed-back) [22,23].…”
Section: Baseline Datasupporting
confidence: 56%
“…The metal tube was connected to a differential pressure transducer and PImax tracings were recorded in real time. Nose clips were worn and patients performed a minimum of 10 efforts to minimise the learning effect [14] with rest intervals of 30-60 seconds between efforts [31,32]. Visual feedback and strong encouragement were given throughout.…”
Section: Maximum Inspiratory Pressure (Pimax)mentioning
confidence: 99%
“…These tests are relatively easy to perform and the development of portable devices has allowed their assessment in a variety of clinical settings. SNIP is a more natural manoeuvre than the PI max or PE max manoeuvres [2] and is used as an outcome measure in clinical studies, such as in patients with degenerative neuromuscular disease [3,4] or chronic obstructive pulmonary disease (COPD) [5]. Due to its volitional nature, the SNIP, just like PI max and PE max , requires a period of familiarisation before baseline measurements are accepted.…”
Section: Introductionmentioning
confidence: 99%
“…The repeatability of SNIP has been studied in healthy subjects [4,7]. In a study by Maillard et al [7], SNIP values obtained after 1 day were maintained after a period of 1 month, and Terzi et al [4] showed that SNIP had good reproducibility over 2 sessions a few days apart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation